Kv1.5 in the Immune System: the Good, the Bad, or the Ugly? - Felipe, Antonio; Soler, Concepció; Comes, Núria (Frontiers in Physiology, 2010)
For the last 20 years, knowledge of the physiological role of voltage-dependent potassium channels (Kv) in the immune system has grown exponentially. Leukocytes express a limited repertoire of Kv channels, which contribute to the membrane potential. These proteins are involved in the immune response and are therefore considered good pharmacological targets. Although there is a clear consensus about the physiological relevance of Kv1.3, the expression and the role of Kv1.5 are controversial. However, recent reports indicate that certain heteromeric Kv1.3/Kv1.5 associations may provide insight on Kv1.5. Here, we summarize what is known about this issue and highlight the role of Kv1.5 partnership interactions that could be responsible for this debate. The Kv1.3/Kv1.5 heterotetrameric composition of the channel and their possible differential associations with accessory regulatory proteins warrant further investigation.